Pemahaman Penjumlahan Dengan Metode Jarimatika Pada Kelas X SMA Negeri 1 Kota Metro - Bahariawan Bahariawan (Jurnal Dewantara, 2018)
Metode Jarimatika is a method with a finger that is fun, because it can attract students so that the activity and learning outcomes increase. This study uses Classroom Action Research (CAR), based on four steps: Planning; Take action; Observation observation; Reflection. With these results, the learning with the Metode Jarimatika can be said to be complete because more than 75% target at the end of the cycle. Based on differences in learning outcomes of cycles I and II can be concluded that the application of Metode Jarimatika can improve students' understanding of mathematics subjects. Learning activity in the first cycle of 56.53% and cycle II 91.31%, thus the learning activity of students increased from cycle I to cycle II of 34.78%. While the learning result completeness level for the first cycle of 35.29% and on the second cycle of 100%, thus the learning outcomes of students experiencing improving from cycle I to cycle II of 64.71%.